Efficacy of Moderate Intensity Statins in the Treatment of Dyslipidemia in Korean Patients with Type 2 Diabetes Mellitus - Sung Hye Kong (Diabetes & Metabolism Journal, 2017)
BackgroundThere has been evidences of ethnic differences in the low density lipoprotein cholesterol (LDL-C) lowering effect of statin. We aimed to evaluate the efficacy of moderate-intensity statins in the treatment of dyslipidemia among Korean patients with type 2 diabetes mellitus (T2DM).MethodsWe analyzed a retrospective cohort that consisted of Korean patients with T2DM aged 40 to 75 years who had been prescribed any of the moderate-intensity statins (atorvastatin 10 or 20 mg, rosuvastatin 5 or 10 mg, pitavastatin 2 mg, or pravastatin 40 mg). Among them, only patients with baseline lipid profiles before starting statin treatment were selected, and changes in their lipid profiles before and 6 months after statin therapy were analyzed.ResultsFollowing the first 6 months of therapy, the overall LDL-C reduction was −47.4% (interquartile range, −56.6% to −34.1%). In total, 92.1% of the participants achieved an LDL-C level of <100 mg/dL, 38.3% had a 30% to 50% reduction in their LDL-C levels, and 42.3% had a reduction in their LDL-C levels greater than 50%. The response rates of each drug for achieving a LDL-C level <100 mg/dL were 81.7%, 93.1%, 95.0%, 95.0%, 96.5%, and 91.7% for treatment with atorvastatin doses of 10 or 20 mg, rosuvastatin 5 or 10 mg, pitavastatin 2 mg, and pravastatin 40 mg, respectively.ConclusionIn conclusion, the use of moderate-intensity statins reduced LDL-C levels less than 100 mg/dL in most of the Korean patients studied with T2DM. The efficacies of those statins were higher than expected in about 42% of Korean patients with T2DM.